Investigating the daylight levels for functional needs in UAE forts. Issue 1 (1st January 2020) - Khoukhi, M.; Gomez, A.M.; Kaabi, S. Al; Shbeikat, W.; Amairi, H.
Abstract: Historic buildings are examples of spaces where daylight was used as a main source of light. A good balance between sufficient daylight and controlled heat gain or loss was achieved in historic buildings. In this research, four different Emirati forts and citadels located in the same climatic region are chosen to assess their daylight illuminance levels. The illuminance levels of the selected spaces of these forts are compared with each other and then compared with the Illuminating Engineering Society of North America (IESNA) standard to determine the lighting preference of the Emirati people against the universal standards. Findings reveal among the four investigated spaces two of them are above the required level of illuminance based on international standards for reading and writing tasks. These buildings are prototypes from which a window-to-floor ratio can be extracted as a good indicator for energy-saving criteria.